SELF-ASSESSMENT OF THE SEX LIFE OF MEN SERVING A PRISON SENTENCE AND A SENSE OF PSYCHOPHYSICAL SECURITY AS PREDICTORS OF THE REHABILITATION PROCESS - Bartoszewski, Jakub; Piestrzyński, Wojciech; Sarzała, Dariusz; Kowalik, Krzysztof (Social work and education, 2020)
This article addresses issues related to the self-assessment of the sex life of prisoners, including selected aspects of their sense of security in the psychophysical sphere. It presents the results of research on the correlates of the sense of security with the individual elements of the sex life of prisoners.